INTERLEUKIN-6 AS A BIOMARKER OF INFLAMMAGING IN AGED RATS (RATTUS NORVEGICUS): A SYSTEMATIC LITERATURE REVIEW - Dessy Abdullah; Rinita Amelia; Ira Suryanis; Melya susanti; Maryetti marwazi; Yudha pratama (Yayasan Nusantara Hasana Berdikari, 2026)
Background: Aging is a complex biological process characterized by declining adaptive capacity, immune dysfunction, cellular damage, and persistent low-grade inflammation known as inflammaging. Interleukin-6 (IL-6) is widely used to assess age-related inflammatory changes; however, findings in aged rat models remain inconsistent and may vary according to strain, age, tissue, sex, metabolic status, and inflammatory stimuli. Objective: This systematic review evaluated changes in IL-6 levels or expression in aging Rattus norvegicus compared with younger rats and explored biological and experimental factors contributing to response heterogeneity. Methods: The review followed the PECO framework and PRISMA 2020 guidelines. Literature searches were conducted in PubMed/MEDLINE, Scopus, Web of Science Core Collection, ScienceDirect, and Google Scholar. Studies involving rats with identifiable age groups and IL-6 as an outcome were included. Risk of bias was planned using the SYRCLE Risk of Bias Tool. Due to substantial heterogeneity in age, strain, tissue, inflammatory stimuli, and IL-6 assessment methods, findings were synthesized narratively. Results: Evidence indicated heterogeneous age-related IL-6 responses. Several studies reported increased IL-6 in aged rats, particularly following lipopolysaccharide stimulation, whereas others found no consistent increase in plasma IL-6 despite increased tissue expression. Conclusion: IL-6 may reflect inflammatory changes during aging, but it is not a universally elevated biomarker in aged rats. Its interpretation should consider tissue compartment, strain, age, sex, metabolic status, and inflammatory stimuli.